HUBUNGAN PROFIL GURU TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA SEKOLAH DASAR DI KECAMATAN INDERALAYA UTARA OGAN ILIR - Yuharto, Yuharto (SCHOLASTICA JOURNAL : JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2018)
ABSTRACTThe Purpose of this research is to determine the relationship between teacher profiles on learning outcomes of secial science elementary school students in the northern Inderalaya sub-district, there are 4 components examined : (Gender, background (academic qualifications), years of service and professional teachers on results studying social scienceelementary school students in in the northern Inderalaya sub-district, Ogan Ilir). This research uses the ex post facto method. The results of this research : 1. There are is no positive and significant relationship between teacher gender dan learning outcomes. 2. There are is no positive and significant relationship between teacher’s final education on learning outcomes. 3. There are is positive and significant relationship between disciplines of learning outcomes. 4. There are is no positive and significant relationship between the duration of the teacher’s teaching experience on the learning outcomes. 5. There are is no positive andsignificant relationship between teacher training/ training and learning outcomes. 6. There are is no positive and significant relationship between professional teachers and learning outcomesKeywordss: Teacher Profile, learning outcomes, Elementary students